2019
DOI: 10.3390/molecules24102016
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Polysaccharide RAP Induces Macrophage Phenotype Polarization to M1 via the Notch Signaling Pathway

Abstract: Macrophages occur in polarized phenotypes, whose characteristics determine the role they play in tumor growth. The M1 phenotype macrophages promote tumoricidal responses and suppress tumor growth. Our previous study showed that a polysaccharide isolated from Radix Astragali, named RAP, was itself non-cytotoxic but induced RAW264.7 cells’ cytotoxicity against cancer cells. The current study was undertaken to determine its mechanism. Series studies was conducted to show that RAP is able to induce much higher gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Astragalus polysaccharide (RAP) was also found to induce the M1 polarization of RAW264.7 cells through the activation of both MAPK and NF-κB signaling pathways. Moreover, the notch signaling pathway proved to be involved in the RAP-induced macrophage M1 polarization [16]. However, the polysaccharide-enriched extract of Echinacea purpurea polarized BMDMs into M1 phenotype only through JNK signaling pathway [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astragalus polysaccharide (RAP) was also found to induce the M1 polarization of RAW264.7 cells through the activation of both MAPK and NF-κB signaling pathways. Moreover, the notch signaling pathway proved to be involved in the RAP-induced macrophage M1 polarization [16]. However, the polysaccharide-enriched extract of Echinacea purpurea polarized BMDMs into M1 phenotype only through JNK signaling pathway [12].…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides from sources of Platycladus orientalis (L.) Franco leaves [11], Echinacea purpurea [12], edible mushrooms ( Pleurotus citrinopileatus ) [13], Cordyceps militaris [14], maca ( Lepidium meyenii ) [15], Astragali Radix decoction ( Astragalus ) [16], and Strongylocentrotus nudus eggs [17] have been found to regulate macrophage polarization. Natural product β- d -glucans, particularly (1→3)-β- d -glucans derived from yeast, fungi, bacteria, or barley, also show immunomodulatory effects and display multiple pharmacological functions through immune regulation [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Using the results in vitro of the clinical samples of the NSCLC cohort it was confirmed that APS can also promote the functional maturation of DCs, enhance the T cell-mediated anti-cancer immune response, and synergistically enhance the therapeutic effect of cisplatin, which proves that it is a substitute in the clinical feasibility of immunotherapy. In addition, further studies by Wei et al (2019) showed that APS induced increased gene expression of M1 markers (including iNOS, IL-6, TNF-α and CXCL10), and induced macrophages to polarize to the M1 phenotype through the notch signaling pathway. In addition, APS can activate macrophages and release NO and TNF-α by activating TLR4 and NF-κB/Rel, directly preventing the growth of cancer cells (Li W. et al, 2019).…”
Section: Astragalus Polysaccharidesmentioning
confidence: 98%
“…(Mantovani et al, 2004;Locati et al, 2013;Tao et al, 2020). Type M2 tumor-associated macrophage (TAM) contributes to tissue repair, tumor angiogenesis, wound healing, and promotes the survival, proliferation, and spread of tumor cells (Wei et al, 2019;Tao et al, 2020). Therefore, in order to balance the level of tumor immunosuppression and immune activation for killing or clearing the tumor, we need to polarize macrophages to M1 or adjust the ratio of M1 to M2.…”
Section: The Regulatory Mechanism Of the Tumor Immune System The Immunomodulatory Mechanism Of Macrophage Cellmentioning
confidence: 99%
“…Proinflammatory M1 macrophages promote tumoricidal response and suppress tumor growth, whereas M2(-like) macrophages contribute to a tumor environment by pampering cancer cell proliferation and survival [22]. Regarding macrophage polarization, Wei et al reported that a polysaccharide isolated from Radix Astragali shifted macrophage phenotype polarization to M1 via the notch signaling pathway to further incite cytotoxic activity of macrophages against cancer cells, as well as decreased tumor volume and tumor weight in vivo [23]. In addition, Ye et al found that 4β-hydroxywithanolide E from Physalis peruviana exhibited anti-colorectal cancer activity in vitro and in vivo by attenuating the wingless-type MMTV integration site family (Wnt)/β-catenin signaling pathway [24].…”
mentioning
confidence: 99%